Clues for two-step virion infectivity factor regulation by core binding factor beta - Ai, Youwei (J Gen Virol, 2017)
Lentiviruses threaten human and animal health. Virion infectivity factor (Vif) is essential for the infectivity of most lentiviruses, except for the equine infectious anaemia virus (EIAV). Vif promotes viral infectivity by recruiting a Cullin-based E3 ligase to induce the degradation of a class of host restriction factors, named APOBEC3. Core binding factor beta (CBF-β) is necessary for several primate lentiviral Vif functions, including HIV-1 Vif. Although much progress has been made in understanding the contribution of CBF-β to Vif function, the precise mechanism has not yet been fully elucidated. In this study, we found that an interaction with CBF-β altered the oligomerization and subcellular distribution pattern and increased the stability of two primate lentiviral Vifs, HIV-1 Vif and Macaca simian immunodeficiency virus (SIVmac) Vif. Moreover, using a CBF-β loss-of-function mutant, we demonstrated that the interaction between CBF-β and Vif was not sufficient for Vif assistance; a region including F68 in CBF-β was also required for the stability and function of Vif. For the first time, this study separates the binding and regulating processes of CBF-β when it is promoting Vif function, which further extends our understanding of the biochemical regulation of Vif by CBF-β.